Identification of Indonesian Products Exported in Their Utilization to Meet the Crude Oil Consumption Level of Thailand through International Trade - Febryana, Sherly; Nursyihab, Dahlia Anggraeni; Oktafiani, Shilvi; Istikhola, Yulfa; Daspar, Daspar (GLOBAL: Jurnal Lentera BITEP, 2024)
In a country, the economy can be measured by the number of goods and services produced in one year. Rapid economic growth increases people's consumption in a country. Apart from carrying out its own production, as a form of global cooperation, a country also requires the role of other countries to meet the consumption needs of its people. This international trade is very profitable for producing and consuming countries. For this reason, Indonesia also establishes trade relations with fellow ASEAN members, such as Thailand. This article aims to identify Indonesia's international trade relations with Thailand as a member of the ASEAN countries. The discussion in this article focuses on the products exported by Indonesia to Thailand as well as the opportunities and threats that arise between Indonesia's international trade and Thailand. However, threats such as increasingly fierce competition, commodity price fluctuations and unstable trade policies also need to be taken seriously.